Signal Scrambling Techniques for PAPR Reduction in OFDM Systems (International Journal of Engineering and Computer Science, 2013)
In recent years, the communication industry has started focusing on fourth generation (4G) mobile communication systems. It is expectedthat 4G will provide a comprehensive and secure IP solution where voice, data, and multimedia can be offered to users at “anytime,anywhere” with higher data rates than previous generations. To improve spectrum efficiency and achieve as high as 100Mbps wirelesstransmission rate, 4G requires more advanced communication techniques to be employed. Multiple input multiple output (MIMO) andorthogonal frequency division multiplexing (OFDM) have, therefore, been adopted due to their superior performance. However, OFDMhas few disadvantages; with the key one is high ratio of peak power of signal to average power is called peak-to-average power ratio;abbreviated as PAPR. It is preferred to have a minimum PAPR, as it will allow a higher average power to be transmitted for a fixed peakpower; and thus, improving the overall signal to noise ratio at the receiver. Therefore, this paper investigates two signal scramblingtechniques, namely, selected mapping (SLM) and partial transmit sequence (PTS) for the purpose of reducing PAPR. From the analysis,it is inferred that PTS method provides a better PAPR reduction performance compared to SLM method. However, the transmitter andreceiver complexity is very high. Thus in practical applications, a tradeoff needs to be made between good performance and auxiliaryinformation. It is also found that SLM algorithm is more suitable if system can tolerate more redundant information; otherwise, PTSalgorithm is more acceptable when complexity becomes the first considering factor.